До старта... после финиша - Васильев Виктор Лазаревич (Физкультура и спорт, 1981)
Экземпляры: КХ (20130314) / Инвентарный номер: 744799 / Цена: 0.55 / Сис.шифр: 796 / Авт.знак: В 19 / ГРНТИ: 77 / ББК: 75.4(2)